2005
DOI: 10.1186/gb-2005-6-13-246
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: SummaryThe AP-2 family of transcription factors consists of five different proteins in humans and mice: AP-2␣, AP-2␤, AP-2␥, AP-2␦ and AP-2⑀. Frogs and fish have known orthologs of some but not all of these proteins, and homologs of the family are also found in protochordates, insects and nematodes. The proteins have a characteristic helix-span-helix motif at the carboxyl terminus, which, together with a central basic region, mediates dimerization and DNA binding. The amino terminus contains the transactivatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
212
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 372 publications
(225 citation statements)
references
References 76 publications
5
212
1
Order By: Relevance
“…In mamma- lian species, e.g. human and rodents, five members of AP-2 factors (␣-⑀) have been reported (11). Among three AP-2 members (AP-2␣, ␤, and ␥) expressed in the nervous system, we show that AP-2␤ specifically regulates development of NA neurons.…”
Section: Ap-2␤ Critically Regulates the Na Neurotransmitter Phenotypementioning
confidence: 75%
See 1 more Smart Citation
“…In mamma- lian species, e.g. human and rodents, five members of AP-2 factors (␣-⑀) have been reported (11). Among three AP-2 members (AP-2␣, ␤, and ␥) expressed in the nervous system, we show that AP-2␤ specifically regulates development of NA neurons.…”
Section: Ap-2␤ Critically Regulates the Na Neurotransmitter Phenotypementioning
confidence: 75%
“…AP-2 proteins share unique structures consisting of an N-terminal transactivation domain and a C-terminal DNA binding and dimerization domain. Although AP-2 proteins are coexpressed in some developing organs, they show different spatiotemporal expression during development, and gene inactivation studies indicated that they may have quite distinct roles in development (11). Based on initial studies of AP-2␣ and its expression in the neural crest (12,13), it was generally assumed that AP-2␣ regulates differentiation of neural crest-derived cells such as SA cells.…”
mentioning
confidence: 99%
“…AP-2 is a family of transcription factors containing a helixspan-helix motif for DNA binding at the carboxyl terminus with possible roles in development, the control of apoptosis and cell cycling, and oncogenesis (40,41). Its members are clearly distinct from AP-1 family transcription factors, homo/heterodimers composed of c-Fos, c-Jun, or ATF, which share a b-Zip motif for dimerization and DNA binding.…”
mentioning
confidence: 99%
“…R. Soc. B 283: 20161712 of chordates including C. intestinalis [18,23,24]. When the AP-2 binding site in the reporter construct was mutated, epidermal expression of the reporter gene was completely abolished (figure 1b-d; electronic supplementary material, figure S2), suggesting that the AP-2 binding site is essential for epidermal expression of Ci-CesA.…”
Section: Resultsmentioning
confidence: 99%